Desain Sistem Jaringan Untuk Smart Factory Berbasis Industrial Internet of Things (Iiot) (Jurnal Rekayasa Komputer, 2025)
The Industrial Revolution 4.0 drives the transformation of production systems toward the smart factory concept. Industrial Internet of Things (IIoT) implementation serves as the primary key to creating adaptive, efficient, and intelligent production systems. This study aims to design an optimal network system model to support the performance of IIoT-based smart factories. Utilizing a Research and Development approach, this research develops a network system prototype and model focusing on data transmission effectiveness, security, and scalability. Evaluation results demonstrate that the designed network model enhances IIoT device communication efficiency and delivers a positive impact on industrial productivity.